The transmembrane G protein-coupled CXCR3 receptor-ligand system and maternal foetal allograft rejection. (15th January 2021) - Amabebe, Emmanuel; Anumba, Dilly O.
Abstract: Chronic placental inflammatory lesions lead to poor obstetric outcomes. These lesions often proceed undetected until examination of placental tissues after delivery and are mediated by CXCR3, a seven-transmembrane G protein-coupled receptor, and its chemokine ligands – CXCL9, CXCL10 and CXCL11. CXCR3-chemokine ligand interaction disrupts feto-maternal immune tolerance and activate obnoxious immunological responses similar to transplant rejection and graft-versus-host disease. The resultant chronic inflammatory responses manifest in different parts of the placenta characterised by the presence of incompatible immunocompetent cells from the feto-maternal unit i.e. maternal CD8 + T cells in the chorionic membrane or plate (chronic chorioamnionitis); foetal Hofbauer cells and maternal CD8 + T cells in the chorionic villous tree (villitis of unknown aetiology); maternal CD8 + T and plasma cells in the basal plate (chronic deciduitis); and maternal CD8 + T cells, histiocytes and T regulatory cells in the intervillous space (chronic intervillositis). This review critically examines how the CXCR3-chemokine ligand interaction disrupts feto-maternal immune tolerance, initiates a series of chronic placental inflammatory lesions, and consequently activates the pathways to intrauterine growth restriction, stillbirth, spontaneous abortion, preterm prelabour rupture of membranes, preterm labour and birth. The possibility of interrupting these signalling pathways through the use of CXCR3 chemokine inhibitors to prevent adverse reproductive sequelae as well as the potential clinical utility of CXCR3 chemokines as non-invasive predictive clinical biomarkers are also highlighted. Highlights: Chronic placental inflammatory lesions are mediated by CXCR3 and its chemokines. Chronic placental inflammation lead maternal foetal allograft rejection. Maternal anti-foetal rejection lead to spontaneous preterm labour and birth. Inhibiting CXCR3 and its chemokines can mitigate chronic placental inflammation. CXCR3 chemokines can be predictive biomarkers of chronic placental inflammation.